Pengaruh Citra dan Kualitas Layanan Terhadap Kepuasan dan Minat Kembali Pasien pada Rumah Sakit Umum Daerah Kota Makassar - Khadijah Fauzi Basalamah; Reza Aril Ahri; Muh Multazam (PT.Mantaya Idea Batara, 2021)
Background: Some patients complained about the response from the hospital staff, the waiting time for services was quite long, then some patients also turned out to be reconsidering using the Makassar City Hospital as an option for treatment. This of course can have an impact on decreasing patient satisfaction and interest. This study was conducted to analyze the effect of image and service quality on satisfaction with the patient's interest in returning to the Makassar City Hospital. Methods: This type of research uses an analytical observational method with a cross sectional study design. The sampling method using purposive sampling was carried out on inpatients at the Makassar City Hospital who had met the criteria. In image measurement, service quality stress, satisfaction, and interest in returning are measured using questionnaires. Results: There were 102 respondents involved in this study. Most of the respondents are in the age group of 20-30 years (36.3%), female (57.8%), have a high school education level (37.3%). The results of statistical tests show that there is an effect of service quality (0.036) on patient satisfaction, there is an influence of image (0.013), service quality (0.006), satisfaction (0.013) on patient interest in Makassar City Hospital. However, the image (0.064) has no effect on patient satisfaction at the Makassar City Hospital. Conclusion: Image, service quality, and satisfaction affect the patient's interest in returning to the Makassar City Hospital. The most influential factor on the interest of returning patients in Makassar City Hospital is Citra.